2001
DOI: 10.1093/emboj/20.6.1439
|View full text |Cite
|
Sign up to set email alerts
|

5′ cloverleaf in poliovirus RNA is a cis-acting replication element required for negative-strand synthesis

Abstract: A cloverleaf structure at the 5' terminus of poliovirus RNA binds viral and cellular proteins. To examine the role of the cloverleaf in poliovirus replication, we determined how cloverleaf mutations affected the stability, translation and replication of poliovirus RNA in HeLa S10 translation-replication reactions. Mutations within the cloverleaf destabilized viral RNA in these reactions. Adding a 5' 7-methyl guanosine cap fully restored the stability of the mutant RNAs and had no effect on their translation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
286
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 247 publications
(313 citation statements)
references
References 58 publications
14
286
1
2
Order By: Relevance
“…From this study, the requirement for WNV (Ϫ)-strand RNA synthesis also follows the trend previously established for other flaviviruses (41, 54 -56) and for poliovirus with regard to the requirement for interaction between the 5Ј and 3Ј ends (57)(58)(59). We examined the role of 5Ј-cap as well as CYC motifs for synthesis of WNV RNA of not only (Ϫ)-strand but also of (ϩ)-strand polarity.…”
Section: Discussionsupporting
confidence: 59%
“…From this study, the requirement for WNV (Ϫ)-strand RNA synthesis also follows the trend previously established for other flaviviruses (41, 54 -56) and for poliovirus with regard to the requirement for interaction between the 5Ј and 3Ј ends (57)(58)(59). We examined the role of 5Ј-cap as well as CYC motifs for synthesis of WNV RNA of not only (Ϫ)-strand but also of (ϩ)-strand polarity.…”
Section: Discussionsupporting
confidence: 59%
“…In conclusion, we have shown that the 51-nt CSE is not essential for SIN RNA replication, but it does enhance its efficiency+ Additionally, we have demonstrated that the 59 UTR of the SIN genome is an essential component of the promoter for both plus-and minusstrand RNA synthesis and that the 59 requirements for each of these processes differ+ Our data demonstrate that interaction between the 59 and 39 ends of the alphavirus genome is required for efficient initiation of minus-strand RNA synthesis+ These data, together with the recent reports for dengue virus and poliovirus (You & Padmanabhan, 1999;Barton et al+, 2001;Herold & Andino, 2001), suggest that communication between I. Frolov, R. Hardy, and C.M. Rice host mRNA translation (Gallie, 1998;Imataka et al+, 1998) and RNA virus replication+…”
Section: Discussionsupporting
confidence: 57%
“…To further define the role of the 59 end of the alphavirus genome in RNA replication, we employed complementary in vivo and in vitro approaches+ These methods allowed us to distinguish between defects in plus-and minus-strand RNA synthesis while separating RNA synthetic events from translation+ Our data begin to define the elements required at the 59 end of the genome for initiation of RNA synthesis by the viral replicase+ These findings and previously published data suggest a model for initiation of minus-strand synthesis that may be broadly applicable to plus sense RNA viruses (Barton et al+, 2001;Herold & Andino, 2001)+…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…2; see Fig. S2 in the supplemental material) (19,21,24). Mutant viral RNAs were divided into four groups on the basis of the structural and functional characteristics of particular 3D pol amino acids: mutations of glycine 64, an amino acid involved in the fidelity of viral RNA replication ( Fig.…”
Section: Resultsmentioning
confidence: 99%